Upaya Pedagang Kecil Dalam Meningkatkan Pendapatan Keluarga (Studi Pedagang Kemplang Panggang Di Kecamatan Gandus) - Jp , Jemma Jeni Okta Jp; Murdiati, Eni; Duku, Sumaina (CV. ITTC INDONESIA, 2023)
Thesis entitled Efforts of Small Traders in Increasing Family Income (Study of Kemplang Panggang Traders in Gandus District). The purpose of this research 1) To find out how the economic conditions of roasted kemplang traders in Gandus sub-district. 2) To find out what factors are the drivers and inhibitors of roasted kemplang traders in increasing family income. The method used in this research is a qualitative method with a descriptive approach. In this study, interviews, observation and documentation were used as data collection methods. Methods for data analysis include data reduction, data presentation and conclusion drawing. The results of this study are: First, the economic condition of roasted kemplang traders is getting better with this roasted kemplang business, the traders are greatly helped in increasing family income and meeting daily needs because the opportunity to trade roasted kemplang is very large in increasing income. Second, the supporting and inhibiting factors for traders are the raw materials in making roasted kemplang, weather in the manufacturing process, capital and marketing.